2018
DOI: 10.14715/cmb/2018.64.11.10
|View full text |Cite
|
Sign up to set email alerts
|

MiR-637 suppresses melanoma progression through directly targeting P-REX2a and inhibiting PTEN/AKT signaling pathway

Abstract: MicroRNAs (miRNAs) play important roles in melanoma. Although miR-637 has been suggested to be a tumor suppressor in several cancers, its function in melanoma and the molecular mechanism behind that function remain unclear. In this study, we investigated the role of miR-637 in human melanoma and explored its relevant mechanisms. We found that the expression of miR-637 is significantly downregulated in melanoma tissues and cell lines. While overexpression of miR-637 inhibited melanoma cell proliferation and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
5
13
0
Order By: Relevance
“…Furthermore, reducing the miR‐637 level was sufficient to reverse shcircEPHB4‐induced phenotypes. Studies in other cancers have established miR‐637 as a consistent tumor suppressor [16–18]. In gliomas, Que et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reducing the miR‐637 level was sufficient to reverse shcircEPHB4‐induced phenotypes. Studies in other cancers have established miR‐637 as a consistent tumor suppressor [16–18]. In gliomas, Que et al .…”
Section: Discussionmentioning
confidence: 99%
“…The result is in accordance with the previous report exhibiting that overexpression of miR-637 inhibited proliferation and induced apoptosis [19].…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, the overexpression of miR-637 in MM cells caused a significant reduction in proliferation and autophagy but a promotion in apoptosis, showing a tumor-suppressive role in MM. The result is in accordance with the previous report exhibiting that the overexpression of miR-637 inhibited proliferation and induced apoptosis [17]. In this study, the expression level of miR-637 was first explored in 36 human samples, and it was found that the expression of miR-637 in the bone marrow The cell viability of MM cells after transfecting miR-637 mimics, NC-LV, or NUPR1-LV was determined by CCK-8 assay.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, supporting our previous results, miR-637 was found to target Akt1 and hamper tumorigenesis in both thyroid carcinoma and pancreatic ductal adenocarcinoma (35,36). MiR-637 could also inhibit Akt phosphorylation and promote melanoma progression (37). Remarkably, although several circular RNAs or long non-coding RNAs (lncRNAs) were found to regulate miR-637 through the mechanism of competitive endogenous RNA, few studies have investigated the crosstalk between transcription factors and miR-637.…”
Section: Discussionsupporting
confidence: 77%